2016
DOI: 10.4081/hr.2016.6678
|View full text |Cite
|
Sign up to set email alerts
|

Study on Hydroxyurea Response in Hemoglobinopathies Patients Using Genetic Markers and Liquid Erythroid Cultures

Abstract: Increased expression of fetal hemoglobin (HbF) may ameliorate the clinical course of hemoglobinopathies. Hydroxyurea (HU) is the only inducer approved for the treatment of these diseases able to stimulate HbF production but patients’ response is highly variable indicating the utility of the identification of pharmacogenomic biomarkers in order to predict pharmacological treatment efficacy. To date few studies to evaluate the role of genetic determinants in HU response have been conducted showing contradictory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…It has recently been reported that, in erythroblasts cultured from peripheral blood CD34 + cells of a group of SCD and β-thalassemia patients who were initially not on HU therapy but were subsequently put on prospective HU therapy, HU-induced changes in HbF levels either before or after HU therapy are similar. 42 This finding, together with our results, indicates that HU and blood exchange therapies did not exert lasting genetic effects on bone marrow CD34 + cells of the patients to significantly change HU-induced HbF levels in patient erythroblasts cultured from the CD34 + cells.…”
Section: Discussionsupporting
confidence: 77%
“…It has recently been reported that, in erythroblasts cultured from peripheral blood CD34 + cells of a group of SCD and β-thalassemia patients who were initially not on HU therapy but were subsequently put on prospective HU therapy, HU-induced changes in HbF levels either before or after HU therapy are similar. 42 This finding, together with our results, indicates that HU and blood exchange therapies did not exert lasting genetic effects on bone marrow CD34 + cells of the patients to significantly change HU-induced HbF levels in patient erythroblasts cultured from the CD34 + cells.…”
Section: Discussionsupporting
confidence: 77%
“…Even if predicting sickle cell severity is complex, stroke appears to be the most devastating complication of sickle cell anemia (SCA), affecting up to 30% of children with the disease. Despite the relative frequency of stroke in SCA, few predictors of this risk have been described [38][39][40]. Thus our severity classification based on the "existence or not of the risk of cerebral vasculopathy" enabled us to better characterize the role of genetic modifiers of SCA.…”
Section: Hbf Is Associated With a High Risk Of Cerebra Vasculopathymentioning
confidence: 99%
“…On the contrary, low HbF was associated with vaso-occlusive complications, requiring treatment with hydroxycarbamide. HU or hydroxycarbamide is the only HbF inducer approved for the treatment of SCD [39]. As reported in several studies, HbF levels have a clinically beneficial effect on SCD [40,41].…”
Section: Hbf Is Associated With a High Risk Of Cerebra Vasculopathymentioning
confidence: 99%
“…Hydroxyurea (HYD), is an antimetabolite and antineoplastic agent that is used alone or in combination with itraconazole, clotrimazole, and terbinafine for the treatment of several kinds of cancer and fungal infections [10,11]. It increases fetal hemoglobin concentration and thus decreases the prevalence of severe health crises and urgent blood transmissions in sickle cell anemia patients.…”
Section: Introductionmentioning
confidence: 99%